Water ecosystem health assessment of Zayandeh Rood - Samar Mortazavi; Golnar Makhfi; Akram Karimi; Siavash Rezazadeh; Mohamad Parsi Mehr (Muhandisī-i Bihdāsht-i Muḥīṭ, 2023)
Background:  Heavy metal pollutants in rivers are one of the serious environmental concerns in aquatic ecosystems. Sediments, as an environmental indicator, have an acceptable ability to express the degree of environmental pollution with heavy metals. Therefore, with the aim of evaluating the health of the water ecosystem of Zayandeh Rood, we investigated pollution using sediment indicators. Methods: In this study, the sediments of Zayandeh Rood River were sampled at 17 stations. Metals lead, zinc, iron, cadmium, cobalt, nickel, copper and chromium were measured by acid digestion method with atomic absorption device. Also, land accumulation indices, Nemerow pollution index and ecological risk potential were calculated. Results: The average concentration of metals in sediments is 1762.92 iron, 201.52 nickel, 44.07 zinc, 23.36 cobalt, 28.67 copper, 11.51 lead, 10.09 chromium, and 0.87 cadmium mg/kg. According to the Igeo index, the average concentration of chromium, iron, copper, zinc and lead elements in all stations was lower than the average of the earth's crust, and the concentration of nickel and cadmium in all stations was higher than the background value. In all stations, the ecological risk potential index of cadmium was higher than other elements. Conclusion: Considering the condition of river sediments in terms of cadmium and nickel pollution and their very high ecological risk, it is necessary to comprehensively monitor the river and its living organisms. Also, in order to evaluate its health and ecological risk with the approach of examining the trend of spatial and temporal changes, heavy metal pollution in water and river sediments should be taken into consideration.